FORMATION OF INTELLECTUAL SKILLS IN JUNIOR STUDENTS IN THE PROCESS ARTISTIC DESIGN (Pedagogy of Higher and Secondary Education, 2022)
Forming intellectual ability demands special conditions which helps child to overcome stresses, overstrain, uneasness,schools, fears, connected with the process o f teaching which contributes to propitious climate for fitted developing of pupils personality in the primary school.
Keywords: 1